Beyond GOG258 and PORTEC3: A National Cancer Database analysis of adjuvant therapy for improved survival in high-risk endometrial cancer - Megan E Lander; John Vargo; Runjia Li; G.K. Balasubramani; Ron Buckanovich; Jamie Lesnock; Alison Garrett; Shannon Rush; Paniti Sukumvanich (Gynecologic Oncology Reports)
Purpose: High-risk Endometrial Cancer (EC) treatment decisions have been informed by two large, randomized trials: GOG-258 and PORTEC-3. Directly comparing these studies to determine the optimal treatment strategy remains challenging as neither included all three arms of interest: chemotherapy alone, chemotherapy combined with radiation, and radiation therapy alone. This study addresses this gap by analyzing National Cancer Database (NCDB) data to evaluate the comparative effectiveness of chemotherapy alone, chemoradiotherapy, and radiation therapy alone. Methods: The NCDB was queried for patients with stage II-IVa endometrioid and any stage clear cell or serous EC who underwent primary surgery with hysterectomy between 2004 and 2020. Univariable and multivariable models investigated prognostic factors and overall survival. Propensity weighted analysis adjusted for potential indication bias. Results: 48,831 patients met inclusion criteria. 19,251 received no adjuvant treatment, 8,076 received adjuvant radiation only, 13,418 received adjuvant chemotherapy only, 1,849 received adjuvant concurrent chemoradiation, and 6,237 received adjuvant sequential chemotherapy and radiation. Factors independently associated with improved survival included adjuvant treatment modality, age, race, insurance status, histology, grade, stage, facility type, facility location, and residential setting. Multivariate propensity weighted analysis showed concurrent and sequential chemoradiation significantly improved OS (HR 0.69, 95 % CI 0.0.60–0.80, p < 0.001; HR 0.63, 95 % CI 0.59–0.67, p < 0.001). Conclusion: Chemoradiation is associated with improved OS in high-risk EC patients regardless of various factors. This data suggests chemoradiation as a preferred treatment option, however, prospective trials directly comparing chemotherapy, radiation, and chemoradiation are needed for confirmation.